Studi Kasus Tindak Pidana Pemerkosaan Ayah Terhadap Anak Kandung Di Wilayah Hukum Pengadilan Negeri Rote Ndao - Modokh, Bacri; Manafe, Deddy R. CH.; Dima, Adrianus Djara (Artemis Law Journal, 2024)
The crime of rape is very worrying especially if the victims are children who are still minors, because this affects the psychological development of children and causes trauma for the rest of their lives. In addition, their future becomes bleak and they have no future. The perpetrators of the crime of rape are often people known to the victim, some are even related, and the most concerning is a father who rapes his biological daughter. The conclusions of this study are: (1) The form of legal protection for child victims of rape in the jurisdiction of the Rote Ndao District Court is in the form of assistance from the PPA during the investigation process, the victim gets protection during the trial so as not to be under pressure the victim is returned to the parents after the trial without going through the rehabilitation process. (2) Consideration of Judges in Criminal Sentencing against perpetrators of Rape of biological children in the jurisdiction of the Rote Ndao District Court is appropriate, based on the testimony of witnesses and the confession of the defendant with evidence in the trial, as well as the judge's consideration of matters that aggravate the defendant, accompanied by consideration of matters that can alleviate the defendant, taking into account the relevant laws, and strengthened by the judge's confidence in imposing a fair decision.